Relationship between Individual and Occupational Factors with Musculoskeletal Disorders on Drinking Water Refill Depot Workers in Padang, West Sumatra - Firdani, Fea; Desmalinda, Vivi Sutia; Alfian, Azyyati Ridha (Universitas Teuku Umar, 2024)
Refill Drinking Water Depot workers rely on physical strength to work, so they are at risk of experiencing Musculoskeletal Disorders (MSDs) complaints. Based on the initial survey, 13 out of 15 workers (86.7%) experienced MSDs. This research aims to determine the relationship between individual and work factors and MSD complaints among refill drinking water depot workers in Padang City. The study used a cross-sectional design. We collected data from November 2022 to July 2023 with a sample of 83 people, selected using proportional random sampling techniques. The dependent variable in this study is complaints of Musculoskeletal Disorders (high risk if NBM score > 20). The independent variables are age (at risk ³ 35 years), work period (at risk ³ five years), smoking habits (at risk if IB values ³ 200), Working posture (at stake if REBA score ³ 7), physical workload (at risk if ³ 100 beats/minute) and BMI (at risk if < 17 and > 25). Data analysis uses univariate and bivariate analysis (chi-square test). The results of the study showed that 71.1% of workers experienced MSD complaints, 34.9% of workers with a risky age, 19.3% of workers with a problematic work period, 32.5% of workers had a smoking habit, 9.6% of workers with a risky BMI, all workers are not at risk of physical workload and 56.6% of workers work with dangerous work postures. The bivariate test results showed that there was no significant relationship between the variables age (p=0.954), years of service (p=0.192), smoking habits (p=0.233), BMI (p=0.330), and work posture (p=0.499) with complaints of MSD. There was no relationship between age, length of service, smoking habits, BMI, and work posture with MSD complaints. We recommended that business owners collaborate with the Community Health Center to provide education about ergonomics when working for refill drinking water depot workers.